Salivary glands in Svalbard reindeer (Rangifer tarandus platyrhynchus) and in Norwegian reindeer (Rangifer tarandus tarandus)
The aim of this investigation was to compare the size of salivaty glands in Svalbard reindeer Rangifer tarandus platyrhynchus) and in Norwegian reindeer (Rangifer t. tarandus) in relation to feeding strategy, season and reproductive status. The mean body mass (BM, standard deviation j) in adult non-lactating female Svalbard reindeer was 72.0